Gambaran Strategi Work-Life Balance Ibu Bekerja di Badan Kepegawaian Daerah Provinsi Sumatera Barat - Banjarnahor, Werni Herninta; Mardianto, Mardianto (YASIN, 2024)
The aim of this research is to determine the work-life balance (WLB) strategy of working mothers at the Regional Civil Service Agency of West Sumatra Province, which has a high category of WLB. This research uses a qualitative method with a descriptive approach. The number of participants in this research was 3 people. Data were analyzed using the Miles & Huberman technique. The findings show that there are 11 themes which are strategies used by subjects in achieving WLB, where these 11 themes include sub-themes, namely as follows. Self management which includes the sub-themes of time management, planning management, priority management, household financial management, and commuting management; Task delegation which includes sub-themes involves extended family support, involves partner support, involves co-worker support, and involves community assistance; Parenting adjustments which include the sub-themes of quality time, maternal role enhancement, child spacing strategy, attachment parenting, increasing children's independence, and managing the number of children; Stress management which includes strategies for spiritual remembrance, self care, habituation, externalizing memory, voluntary career plateauing, dyadic coping, and avoiding task accumulation; Communication strategies that include strategies for providing understanding to children, communicating everything to partners, communication with colleagues, effective communication with superiors, and positive social interactions; Utilizing organizational support which includes strategies for utilizing work flexibility, bringing children to work, utilizing organizational facilities; use of digital technology and communications; Have a positive character that includes a sense of responsibility, self-discipline, gratitude; Intrinsic motivation which includes strategies for making children motivated to work; Emotional intelligence which includes impression management strategies, managing emotions; and the final strategy is utilizing educational background.